2012
DOI: 10.3390/molecules17010786
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Novel meta- and para-Substituted N-Benzyl Protected Quinuclidine Esters and Their Resolution with Butyrylcholinesterase

Abstract: Since the optically active quinuclidin-3-ol is an important intermediate in the preparation of physiologically or pharmacologically active compounds, a new biocatalytic method for the production of chiral quinuclidin-3-ols was examined. Butyrylcholinesterase (BChE; EC 3.1.1.8) was chosen as a biocatalyst in a preparative kinetic resolution of enantiomers. A series of racemic, (R)- and (S)-esters of quinuclidin-3-ol and acetic, benzoic, phthalic and isonicotinic acids were synthesized, as well as their racemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Twenty quaternary derivatives of cinchonidines (CD compounds) and their corresponding pseudo -enantiomers cinchonines (CN compounds) were synthesized following standard procedures for the Menshutkin reaction [ 25 28 ] starting from commercially available cinchonidine (CD) or cinchonine (CN) ( Fig 2 ; detailed in S1 File ). Compounds CD-(mBr), CD-(mMet), CD-(mCl), CD-(mNO 2 ) CN-(pMet), and CN-(mMet) were novel compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty quaternary derivatives of cinchonidines (CD compounds) and their corresponding pseudo -enantiomers cinchonines (CN compounds) were synthesized following standard procedures for the Menshutkin reaction [ 25 28 ] starting from commercially available cinchonidine (CD) or cinchonine (CN) ( Fig 2 ; detailed in S1 File ). Compounds CD-(mBr), CD-(mMet), CD-(mCl), CD-(mNO 2 ) CN-(pMet), and CN-(mMet) were novel compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds were synthesized following standard procedures for the Menshutkin reaction [ 25 28 ] starting from commercially available cinchonidine or cinchonine (≥98.0%, Sigma-Aldrich, St. Louis, MO, USA). Cinchona alkaloid (1 mmol) and appropriate halide (1.05 mmol for para - or 1.2 mmol for meta -substituted benzyl bromide) in toluene were heated to reflux and end of reaction was detected with thin layer chromatography (CHCl 3 : MeOH = 9:1).…”
Section: Methodsmentioning
confidence: 99%
“…The reduced palladium species likely triggered the FUR conversion. The use of acetic acid [97][98][99][100][101] or ammonium formate [102,103] as hydrogen sources instead of FAc, did not give bioPs. Tan et al [99] reported for a commercial palladium catalyst the effective H2 production from FAc, but not from acetic acid; conversely, a commercial nickel oxide catalyst converted acetic acid to H2, albeit at very high temperature (300 ºC).…”
Section: General Considerationsmentioning
confidence: 94%